Application to visualize an ontology for the human semen analysis domain (2007)
This paper presents the design and implementation of an ontology for the domain of human semen analysis, whose objective is to represent, organize, formalize and standardize domain knowledge, so that it can be shared and reused by different groups of people and software applications To visualize the ontology, an application based on a client / server architecture for Web environments was developed, which is constituted by an Administration module and a Public Access module. The ontology website is maintained through the first, while the second allows users to access stored knowledge and a set of resources such as images, videos, domain-related articles, manuals and laboratory protocols. The proposed architecture facilitates the observation and recovery of complex knowledge structures, as well as the navigation and administration of the information represented in the ontology. The approach used in the design of information retrieval mechanisms is aimed both at users unfamiliar with the domain vocabulary, and those who already know it. This functionality is of special interest given the heterogeneity of the audience to which the ontology is directed, such as professionals and students of health sciences, among others. The Methontology methodology was selected to develop the ontology and the Protégé editor was used for its implementation.